PROSES DEPARAFINASI SEDIAAN JARINGAN GINJAL DENGAN DAN TANPA PEMANASAN MENGGUNAKAN MINERAL OIL PADA PEWARNAAN HEMATOKSILIN-EOSIN - Tulus Ariyadi (Jurnal Kesehatan Rajawali, 2021)
Hematoxylin Eosin staining aims to provide easy reading of tissue preparations. In the Hematoxylin Eosin staining stage, one of them uses xylol in the deparaffinization process to remove paraffin from the tissue and the clearing process to clear the tissue before mounting. Xylol is known as a non-polar solution that has many uses but has a toxic effect on health. Mineral Oil is a potential alternative to xylol for deparaffinization and clearing because it has the same non-polar properties as xylol. The purpose of this study was to determine the best mineral oil temperature on the quality of guinea pig kidney tissue preparations. This type of research is descriptive. Samples came from the kidneys of male guinea pigs which were divided into 3 groups. The results showed that the deparaffinization and clearing process using xylol obtained 100% tissue quality with good results, on mineral oil without heating at 0% room temperature the results were not good, on mineral oil with heating temperature of 50°C 100% good results. Based on the results, it was concluded that the use of mineral oil with heating was better and almost the same as the control.